Rapid testing of gut permeability using oral fluorescein and confocal laser endomicroscopy in Zambian adults. (12th June 2021) - Mbuki, Reuben; Chileya, Sandra; Thompson, Alex J; Kelly, Paul; Kayamba, Violet
Abstract: Background: Dual sugar testing for gut permeability is time-consuming and complex. We explored the utility of fluorescein as a simple and inexpensive alternative method. Methods: We used a confocal laser endomicroscopy probe placed at the fingertip of participants who had ingested sodium fluorescein to measure the fluorescence at various time points. Results: In 10 patients with diarrhoea, but not in 10 controls, fluorescence was detected quickly. By 6 min fluorescence was detected in all diarrhoea patients but only 1 control (p=0.0004). After 15 min there was no difference between the groups. Conclusions: This simple oral fluorescein test may be useful to study gut permeability in low-resource settings.